An Italian survey on the use of hypertonic solution in aerosol - Ros, M.; Lucca, F. (Acta Biomedica Atenei Parmensis, 2014)
Hypertonic saline (HS) preceded by a bronchodilator is an inexpensive, safe, and effective additional therapy for patients with cystic fibrosis. A questionnaire composed of 14 closed-ended questions was prepared and sent by email to the Directors of 30 Italian CF Centers for verifying which the indications in CF patients of inhaled HS and HS with hyaluronan (HSHA) are, how tolerability to HSHA is assessed and how compliance and tolerability to HSHA is evaluated.